(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article highlights the psychological aspects of medical sociopsychological rehabilitation of young children with special educational needs. The importance of a balanced harmonious impact on the psyche of a child as a future citizen of modern society is noted. The author pays special attention to the development of sensorimotor, psychomotor neoplasms on the basis of compensatory properties of higher mental functions. The significance of the simulated environment, which influences the sensations of different modality, has been determined. The author cites the results of an empirical study of the behavioral reactions of pupils of the Children’s Home. The relevance of the systemic modeling of the correctional environment as a factor influencing the quality of certainty of the child’s feelings has been proved.